Analyzing the Potential Benefits of Brand Ambassador Marketing - Chen, Feitong (Transactions on Economics, Business and Management Research, 2024)
Prada's lackluster performance in the Chinese market in recent years can be attributed to its marketing plan errors. Prada launched a new collaboration with the Chinese Women's Football Team on July 10, 2023. The objective of this study was to examine the impact of the recent collaboration on Prada's business growth in the Chinese market. This study employed data from Chinese consumers, financial reports from the Prada Group, and relevant studies to clarify this subject and ultimately reach a conclusion. By employing brand ambassadors, Prada may improve its unfavorable brand image and boost its online engagement with consumers, resulting in further advantages. The new collaboration allows Prada to strengthen customer loyalty to its brand. To increase the probability of customers making repeat purchases, Prada should offer exceptional designs in its unique collections for the football team. Furthermore, this collaboration enables Prada to broaden its market penetration. In order to enhance its performance, Prada should enhance its aesthetic and provide a wider range of prototype products for its brand ambassadors. This article enhances and supplements the current research on the brand ambassador marketing strategy. Additionally, this report provides guidance to luxury brands regarding novel marketing methods.